Comparative Success Rates in Fund Allocation for Social Enterprise Subsidies in Romania: Rural vs Urban Dynamics in 2024 - Simona-Beatrice Manolache; Cristian Marian Radu (Journal of Agriculture and Rural Development Studies, 2024)
The allocation of funds for social enterprise subsidies is a critical mechanism in advancing social entrepreneurship, particularly in countries like Romania, where social enterprises play a significant role in fostering community resilience and economic inclusion. In 2024, Romania continues prioritizing these subsidies, with a growing focus on equitable development across rural and urban regions. However, the dynamics of fund allocation differ considerably between these settings due to varying economic structures, infrastructure, and the capacity of social enterprises to attract and manage funding. This article examines the comparative success rates in fund allocation for social enterprises in rural versus urban areas. The study shows a coordinated effort between EU and national funds to support various development projects in Romania. The analysis highlights the need to address regional and sectoral disparities in fund allocation, better support rural projects, and improve the overall quality of projects to maximize long-term social and economic impact. Investments in the social economy must continue, given their crucial role in reconciling economic, social, and financial dimensions. However, increasing attention to sustainability and equity in resource distribution is essential.